Surging Investment and Declining Aid : Evaluating Debt Sustainability in Rwanda - Clark JR, John (IMF Working Papers; Working Paper ;, 2014)
Rwanda is a unique case among its Sub-Saharan African peers in that it has already undergone a large scaling-up of public investment. The Rwandan government has made clear its desire to lower its reliance on foreign aid while still maintaining high public investment levels. We use the model of public investment, growth, and debt sustainability in Buffie and others (2012) to evaluate the macroeconomic consequences of a possible scaling-down of investment in Rwanda. Using the model, we can gauge the consequences of different financing mechanisms and investment efficiency levels on the economy. We find that with some commercial borrowing and a modest tax adjustment, the authorities may be able to retain their high investment spending while still reducing their reliance on foreign aid.